System-level factors influencing refugee women's access and utilization of sexual and reproductive health services: A qualitative study of providers’ perspectives - Vu, Milkie; Besera, Ghenet; Ta, Danny; Escoffery, Cam; Kandula, Namratha R.; Srivanjarean, Yotin; Burks, Amanda J.; Dimacali, Danielle; Rizal, Pabitra; Alay, Puspa; Htun, Cho; Hall, Kelli S. (Frontiers in Global Women's Health, 2022)
Refugee women have poor outcomes and low utilization of sexual and reproductive health (SRH) services, which may be driven by access to and quality of SRH services at their resettled destinations. While healthcare providers offer valuable insights into these topics, little research has explored United States (U.S.) providers' experiences. To fill this literature gap, we investigate U.S. providers' perspectives of healthcare system-related factors influencing refugee women's access and utilization of SRH services. Between July and December 2019, we conducted in-depth, semi-structured interviews with 17 providers serving refugee women in metropolitan Atlanta in the state of Georgia (United States). We used convenience and snowball sampling for recruitment. We inquired about system-related resources, facilitators, and barriers influencing SRH services access and utilization. Two coders analyzed the data using a qualitative thematic approach. We found that transportation availability was crucial to refugee women's SRH services access. Providers noted a tension between refugee women's preferred usage of informal interpretation assistance (e.g., family and friends) and healthcare providers’ desire for more formal interpretation services. Providers reported a lack of funding and human resources to offer comprehensive SRH services as well as several challenges with using a referral system for women to get SRH care in other systems. Culturally and linguistically-concordant patient navigators were successful at helping refugee women navigate the healthcare system and addressing language barriers. We discussed implications for future research and practice to improve refugee women's SRH care access and utilization. In particular, our findings underscore multilevel constraints of clinics providing SRH care to refugee women and highlight the importance of transportation services and acceptable interpretation services. While understudied, the use of patient navigators holds potential for increasing refugee women's SRH care access and utilization. Patient navigation can both effectively address language-related challenges for refugee women and help them navigate the healthcare system for SRH. Future research should explore organizational and external factors that can facilitate or hinder the implementation of patient navigators for refugee women's SRH care.